Validation of an Indigenous Technical Knowledge (ITK) against the Epizootic Ulcerative Syndrome (EUS) of Fish - Debnath, Chandan; Sahoo, Lopamudra; Debnath, Biswajit; Ngachan, S. V. (Indian Journal of Hill Farming, 2018)
Epizootic ulcerative syndrome (EUS) is a major setback in Fisheries with almost no cure. A farmer of Sabroom, South Tripura District developed a concoction of 8 kg mustard oil cake, 4 litre kerosene and 1½ kg soil for a hectare pond against this disease with encouraging result. We have visited the site, collected samples and validated the finding. The mixture was found enhancing the immunity and disease resistance of fish without affecting the water (temperature, dissolved oxygen, alkalinity, ammonia, nitrate, phosphate, nitrite and transparency), soil (pH, OC, available N and available P), plankton and proximate composition of fish. Blood glucose was significantly minimized, whereas, serum protein, enzyme, respiratory burst (NBT), lysozyme and bactericidal activity were increased (p≤0.05). Erythrocytes, leukocytes and hemoglobin content of the blood were also improved (p≤0.05). The mixture is easy to prepare and use; it requires single dose at last week of November. It is further eco-friendly and cost-effective (Rs. 690/ha), thus, suggested against the EUS.